Damage Identification of Prefabricated Reinforced Concrete Box Culvert Based on Improved Fuzzy Clustering Algorithm and Acoustic Emission Parameters - Gong, Yafeng; Lin, Siyuan; He, Feng; He, Yang; Song, Jiaxiang (Advances in materials science and engineering, 2021)
Prefabricated box culvert is a new structure in road engineering, whose health is very important to road safety. The use of acoustic emission (AE) as a detection method and the use of other improved algorithms to evaluate the damage of prefabricated box culverts are still insufficient. In this paper, two kinds of prefabricated box culverts are tested and studied, and the damage process of the box culverts is analysed based on the AE parameters of the box culvert using the traditional fuzzy C-means method (FCM). In addition, an improved algorithm based on the combination of grid density and distance (G-DFCM) was proposed, which was simulated and applied to the AE data analysis of the prefabricated box culvert. The research results show that the application effect of the G-DFCM algorithm is good, which not only overcomes the shortcomings of the original algorithm but also improves the effectiveness of the algorithm. This work can provide a supplement to the damage identification of fabricated box culverts.